Comunicación, redes sociales y discriminación. Caso Danna Sultana - Vera Triana, Roxana Anabell (2021)
The following is a case study that addresses issues of common interest such as Communication, Social Networks and Discrimination. The objective is to analyze the discourse of gender discrimination in young people and social networks which affects people of different genders through offensive comments, emoticons, GIFs, stickers and images. In addition, it will identify the problems that exist today in terms of the need for young people in social networks, their lack of morals and ethics when addressing any human being regardless of religion, sex, culture and skin color. Despite being in any media does not mean that they have the power to show their feelings towards the other person and the way they communicate nowadays through internet platforms. We will also analyze a result obtained through interviews with different public officials and people belonging to the transgender community that will help us to confirm the theoretical support, taking into account that today the cybernetic modality has changed a lot in the lives of people, both men and women to people of the LGBTI community in general who suffer cyber violence. The conclusion is that the use of communication that exists in social networks at the time of transmitting a message and the same way that reaches the other person in a good or bad intentioned way and what it can create without knowing the motives of other people. Finally, as a recommendation, it is established that gender discrimination is a reality in social networks and strategies should be applied to achieve good communication, even so that there is not so much discrimination in social networks and through them to achieve virtual training on vulnerable groups.